Determination of Some Morphological Characteristics of the Kyrgyz Taigan Dog Breed - Ari, Hasan Huseyin; Tas, Abuzer; Sen, Ismail; Bayraktar, Metin; Garip, Mustafa; Begaliev, Aziz; Salykov, Ruslan (Wiley, 2025)
This study involved morphological measurements of the body and head of 77 male and female Kyrgyz Taigans aged 12-16, 24-30 and 36+ months (denoted as groups 1, 2 and 3, respectively). Length measurements (head, face and ear) were obtained using an electronic calliper; width measurements (head, face and pinna) and circumference measurements (head, neck, chest, waist and front and rear shins) were taken using a measuring tape; and height measurements (withers and rump) were obtained using a measuring stick. IBM SPSS 22 was used for statistical analysis, and descriptive statistics of the groups were obtained. Student's t-test was used for between-group comparisons (gender), ANOVA for multiple-group comparisons (age), and the Tukey test for post hoc analysis. The average measurements for face, ear, tail, head, neck, front and rear shins, body length, and height were compared, and significant differences (p < 0.05) were observed between the male and female dogs in the three groups. Significant differences in neck, waist and chest circumferences and chest width and depth were also observed (p < 0.05). The Kyrgyz Taigan is a medium-sized dog breed in terms of body weight, is long-headed (dolichocephalic), exhibits a rectangular body shape similar to other greyhound breeds, and has a rump and withers that are of similar heights. Compared with other greyhound breeds, the Kyrgyz Taigan has greater values for head length, withers and rump heights, chest circumference and chest depth.
Keywords: body measurements; head measurements; Kyrgyz Taigan; morphometric characteristics